Psychological Well- Being and Work-Life Balance in Female Civil Servants at BKKBN of South Sumatera Selatan - Hidayat, Rahmat; Arisandy, Desy (Yayasan Mata Pena Madani, 2024)
This study was conducted to determine the relationship between psychological well- being and work-life balance in female ASNs at the BKKBN Representative of South Sumatra Province. the sample in this research was 267 female ASNs at the BKKBN Representative of South Sumatra Province. The sample technique used in this study was the Simple Random sampling technique. The measuring instruments used are the psychological well- being scale and the work-life balance scale. The analysis technique used is simple regression using SPSS Version 20.0. The results of the analysis show the correlation coefficient (r) = 0, 997 with the score obtained, namely (R-Square) = 0, 994 and p = 0.000 (p 0.05 and p 0.01) which means that the proposed hypothesis is accepted. these results indicate that there is a very significant relationship between psychological well being and work-life balance in female ASNs at the BKKBN representative of South Sumatra Province.